Resonance frequency analysis-reliability in third generation instruments: Osstell mentor® - Herrero-Climent, Mariano (Medicina Oral S.L., 2012)
Few studies assess repeatability and reproducibility in registers of resonance frequency analysis (a value of dental implant stability). Objective: Few studies assess repeatability and reproducibility in resonance frequency analyses (implant stability evaluation). This study is aimed at assessing reliability (repeatabilty and reproducibility) in the Osstell Mentor® system using the intraclass correlation coefficient (ICC) as the statistical method. Study Design: ISQ measurements of RFA were carried out by means of the Osstell Mentor® instrument in 58 implants in 19 patients. Six measurements were performed on each implant by means of two different Smart-Pegs (I and II). Three consecutive measurements were registered with each transducer. Results: Average ISQ varied from 72.43 to 72.60 and 73.26 in the first, second and third measurements, respectively with the SamrtPeg I and from 72.98 to 73.26 and 73.74 in the first, second and third measurements, respectively with the SamrtPeg II . Exactly equal values were observed in 10.43 and 12.1% of the cases with Smart-Pegs I and II, respectively. The intraclass correlation coefficient was 0.96 and 0.96 for Smart Pegs I and II, respectively. Repeatability and reproducibility was 0.97 for both Smart-Pegs I and II. Conclusions: The RFA system contributed by Osstell Mentor® renders almost perfect reproducibility and repeatability, as proven by statistical analysis carried out by means of ICC with 95% confidence level. This instrument contributes highly reliable RFA measurements in dental implants. Key words:Dental implants, RFA, ISQ, implant stability, Osstell.